Growing Green. Environmental issues and ecological sensitivity in Italian unscripted TV - Carelli, Paolo (Green Narratives, Ecology and Sustainability in Contemporary Television - Exploring Narrative Ecosystems, 2025)
Green topics are constantly growing in the field of media, both in production policies made up by producers and companies, and in representation styles of media content such as movies, documentaries, TV series and TV programs. However, while in scripted products these themes seem to impose themselves with greater difficulty due to complex attempts to integrate them into autonomous storylines, unscripted TV reveals as a potential genre to spread issues related to sustainability and green and environmental challenges. Based prevailingly on real settings and people and aimed at narrating aspects and situations near to everyday life, unscripted TV could represent an ideal space to represent green and eco-friendly topics more directly than scripted programs. T he essay wants to explore the role of green issues in Italian unscripted television; since the so-called “TV of the origins”, green and environment aspects have often characterized programmes such as reportages, documentaries, cultural and scientific TV magazines and many other genres. In recent years, due also to the proliferation of thematic channels and streaming platforms, the theme of “green” has grown with a lot of dedicated programmes of diversified genres and points of view about a complex and multifaceted theme, from the climate change to the fight against food waste, from the exploitation of food and wine traditions to the preservation of natural landscapes and biodiversity. In many recent cases, “green” has become a keyword able to identify the title of the programs (from Rai’s Play Green to Mediaset’s Green Storytellers, until Warner Bros’ Discovery’s Green Table), shaping a new trend that refers explicitly to a renewed sensitivity about a global problem.